Pengaruh Kecepatan Udara pada Alat Pengering Jagung dengan Mekanisme Penukar Kalor - Alit, Ida Bagus; Susana, I Gede Bawa (Jurnal Rekayasa Mesin, 2020)
The purpose of this study was to design and determine the performance of a dryer for drying corn with biomass burning energy sources. The dryer consists of a biomass stove, a heat exchanger, and a drying cabinet. The dimensions of the biomass stove are 500 x 500 x 800 mm with a diameter and hole distances of the biomass stove wall is 10 mm and 50 mm, respectively. The heat exchanger pipe diameter is 25.5 mm, the drying cabinet 500 x 500 x 600 mm, and the biomass was rice husk. The heat exchanger is made of stainless steel pipes arranged in a parallel arrangement. A heat exchanger pipe connects the biomass stove to the drying cabinet in order to avoid drying products from burning biomass contamination. The results showed that the drying rate could be faster if the air velocity increases. Drying corn in order to reduce water content from 19% to 12% takes 47 minutes with an air velocity of 3 m/s.